Longer disease progression milestone-free time in people with amyotrophic lateral sclerosis treated versus not treated with intravenous edaravone: results from an administrative claims analysis - James D Berry; Melissa Hagan; Jeffrey Zhang; Ying Liu; Malgorzata Ciepielewska (Journal of Comparative Effectiveness Research)
Aim: To estimate time-to-progression milestones in people with amyotrophic lateral sclerosis (PALS) treated versus not treated with intravenous (IV) edaravone (Radicava R IV, Mitsubishi Tanabe Pharma America [MTPA], hereafter ”IV edaravone”) in a real-world setting. Background: IV edaravone is US FDA approved for the treatment of ALS and was shown in clinical trials to slow the rate of physical functional decline. Patients & methods: This retrospective observational analysis included PALS continuously enrolled in Optum’s Clinformatics Data Mart between 8 August 2017 and 31 December 2021. Cases treated with IV edaravone and controls not treated with IV edaravone were propensity score matched for: age, sex, race, US region of residence, pre-index disease duration, insurance, riluzole prescription; and preindex claims for cardiovascular disease, artificial nutrition/gastrostomy tube, noninvasive ventilation and all-cause hospitalization. The index date was the first IV edaravone claim for cases; for controls, the index date was randomly assigned after IV edaravone market availability. Restricted mean time lost was calculated for the following disease progression milestones: new use of canes/walkers/wheelchairs, artificial nutrition, noninvasive ventilation, invasive ventilation, speech-generating devices and hospice. Results: Cases (n = 395) were matched to controls (n = 395). Cases had less restricted mean time lost, indicating longer disease progression milestone-free time, for all disease progression milestones. From 0 to 24 months post index, more cases (n = 129) than controls (n = 103) reported no milestones and more controls (n = 232) than cases (n = 131) reported deaths. Conclusion: In a US-based real-world setting, IV edaravone-treated PALS had a longer time to disease progression milestone events and fewer deaths in 2 years compared with PALS not treated with IV edaravone.